2020
DOI: 10.1021/acsomega.0c04489
|View full text |Cite|
|
Sign up to set email alerts
|

Melissa officinalisExtract Induces Apoptosis and Inhibits Migration in Human Colorectal Cancer Cells

Abstract: Colorectal cancer (CRC) is one of the most frequently diagnosed cancers worldwide. Lifestyle-related factors, such as diet, are associated with the development of CRC. Cumulating evidence indicates noticeable chemopreventive effects of phytochemicals on CRC, suggesting that drinking herbal tea potentially reduces the risk of distal colon cancer via its antiproliferative and anti-angiogenic activities. We examine the antitumor effects of nine components frequently found in herbal tea and uncover the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Depletion of MMP is one of the mitochondria-mediated apoptosis hallmarks [ 27 ]. Combing our previous finding of MO-triggered apoptosis [ 11 ] and decreased ETC proteins discovered by the proteomics analysis, we ought to explore whether MO-induced CRC apoptotic cell death is related to mitochondrial dysfunction. To this end, we treated HCT116 cells with 375 µg/mL MO for 48 h and measured MMP using JC-1 dye to assess mitochondria integrity.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Depletion of MMP is one of the mitochondria-mediated apoptosis hallmarks [ 27 ]. Combing our previous finding of MO-triggered apoptosis [ 11 ] and decreased ETC proteins discovered by the proteomics analysis, we ought to explore whether MO-induced CRC apoptotic cell death is related to mitochondrial dysfunction. To this end, we treated HCT116 cells with 375 µg/mL MO for 48 h and measured MMP using JC-1 dye to assess mitochondria integrity.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, we revealed that the hot water MO extract showed anticancer activity in HCT116 CRC cells [ 11 ]. Here, we applied proteomic analysis to comprehensively investigate the inhibitory molecular mechanism of MO on CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemon balm aqueous extracts were reported to elicit antitumor effect in various cancer cell lines, namely breast adenocarcinoma [12], colon cancer [64], prostate cancer [65] and others. The existent scientific data do not offer sufficient information regarding the effect of aqueous lemon balm extracts on melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of cancer patients is increasing due to population growth and aging [5]. Recently, researchers demonstrated rapid advances in the field of cancer therapy, where genetic alterations and the dysfunction of signal transduction pathways play important roles in cancer development [6][7][8]. Although cancer development's underlying mechanisms have been extensively studied, CRC patients in particular are still coping with low survival rates.…”
Section: Introductionmentioning
confidence: 99%